The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00542-012-1462-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal-based piezoelectric microelectromechanical systems scanner composed of Pb(Zr, Ti)O3 thin film on titanium substrate

Abstract: We have developed a titanium (Ti)-based piezoelectric microelectromechanical systems scanner driven by a Pb(Zr, Ti)O 3 (PZT) thin film for the development of laser scanning displays. The 2-lm-thick PZT thin film was directly deposited on a 50-lm-thick Ti substrate by radio frequency magnetron sputtering. Prior to PZT deposition, the Ti substrate was microfabricated into the shape of a horizontal scanner by wet etching; therefore, we could fabricate a piezoelectric microactuator without using the photolithograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Park et al introduced a stainless steel based piezoelectric scanner operating at 28.24 kHz [88]. Moreover, Matsushita et al developed a 25.4 kHz PZT film actuated scanner on a Ti substrate to simplify the fabrication process of piezoelectric thin film MEMS [91]. Both these metal-based scanners showed good control of dynamic deformation.…”
Section: Piezoelectrically Actuated Scannersmentioning
confidence: 99%
“…Park et al introduced a stainless steel based piezoelectric scanner operating at 28.24 kHz [88]. Moreover, Matsushita et al developed a 25.4 kHz PZT film actuated scanner on a Ti substrate to simplify the fabrication process of piezoelectric thin film MEMS [91]. Both these metal-based scanners showed good control of dynamic deformation.…”
Section: Piezoelectrically Actuated Scannersmentioning
confidence: 99%
“…It should be noted that some recent studies have reported new types of piezoelectric micro-electromechanical systems such as piezoelectric micro-mirrors actuated by Nb-doped PZT thin films [11,12] and metal-based scanner [13] with flexible piezoelectric micro/nano-actuators [14,15], where various advanced processing methods, such as ultrasonic processing, slow machining processing and 3D printing, have been successfully applied to the fabrication of micro/nanopositioning stages with more DOF and flexibility [16]. For example, a two-axis optical scanner based on the stainlesssteel substrate and piezoelectric thin sheets have been developed and fabricated as an alternative to designing microscanners with a larger mirror size and scanning angle at the middle frequency range [17].…”
Section: Introductionmentioning
confidence: 99%
“…A MEMS mirror has been widely used for laser=light scanning systems such as optical switches, 1,2) bar code scanners, 3) projection displays, [4][5][6] endoscopes, 7) confocal laser scanning, 8,9) and optical coherent tomography. [10][11][12] Recently, in addition to one-and two-dimensional (1D=2D) MEMS mirrors, a 3D MEMS mirror has been developed for application in an optical phase modulation or a 3D optical projection=imaging.…”
Section: Introductionmentioning
confidence: 99%